2018
DOI: 10.1039/c8tb00748a
|View full text |Cite
|
Sign up to set email alerts
|

Targeted multifunctional redox-sensitive micelle co-delivery of DNA and doxorubicin for the treatment of breast cancer

Abstract: Drug/gene co-delivery carriers are a promising strategy for cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…Caspases are essential mediators of programmed cell death and they are triggered sequentially, in which activation of Caspase 12 leads to the activation of Caspase 9 and the subsequent ‘effector’ Caspase 3 59 . Both DOX and DOX-EDT-IONPs treatments upregulated the Caspase 3 gene expression, which is consistent with its upregulation in C6 glioma 10 , leukemia HL-60 60 , and MCF-7 breast cancer 61 cells upon DOX treatments. p53 is a tumor suppressor protein whose mutation is the most prevalent genetic alteration in human cancers 62 .…”
Section: Resultssupporting
confidence: 76%
“…Caspases are essential mediators of programmed cell death and they are triggered sequentially, in which activation of Caspase 12 leads to the activation of Caspase 9 and the subsequent ‘effector’ Caspase 3 59 . Both DOX and DOX-EDT-IONPs treatments upregulated the Caspase 3 gene expression, which is consistent with its upregulation in C6 glioma 10 , leukemia HL-60 60 , and MCF-7 breast cancer 61 cells upon DOX treatments. p53 is a tumor suppressor protein whose mutation is the most prevalent genetic alteration in human cancers 62 .…”
Section: Resultssupporting
confidence: 76%
“…Wei Hong et al successfully synthesised pHresponsive copolymers based on PLGA-PEG-PLGA and poly(Lhistidine) and achieved predominant antitumor effect in vitro [39]. In additional, Longbao Feng et al successfully developed a novel T7-conjugated redox-sensitive targeting amphiphilic molecule (PEG-PEI-PCL-SS-PCL-PEG) to co-deliver DOX and TRAIL, which showed a higher antitumor efficiency in vivo [18].…”
Section: Cellular Uptake Testsmentioning
confidence: 99%
“…As the biomaterial approved by the Food and Drug Administration (FDA), poly (lactide-co-glycolides) (PLGA) can be degraded into non-toxic lactic acid in vivo, which was ranked as one the most popular biodegradable polymers due to its longterm clinical application, favourable degradation characteristics and sustained release ability [15][16][17]. Besides, the hydrophilic block of poly(ethylene glycol) (PEG) could prolong the systemic circulation time and minimize opsonization which leads to the non-specific uptake in normal tissue [18]. There are large number of previous studies that concerning PLGA-PEG micelles used for glioma treatments, which have been confirmed to have controllable particle size, good biocompatible, reduced systemic clearance and high capacity of drug loading [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…DOX/TRAIL codelivery was augmented when Tf receptors (TfR) were targeted by utilizing oligopeptide HAIYAPRH (Bertrand, Wu, Xu, Kamaly, & Farokhzad, 2014;Oh, Kim, Singh, Lai, & Sasaki, 2009). Most notably, intravenous DOX/TRAIL codelivery with this redox-sensitive polymer in BALB/c nude mice bearing subcutaneous MCF-7 breast tumors significantly inhibited tumor growth relative to single modality treatments (L. Feng et al, 2018).…”
Section: Functionalization and Targeting Of Cationic Polymersmentioning
confidence: 99%
“…(b) Synthesis of the PEI‐PEG‐TAT system for delivery of plasmid DNA (pDNA) encoding TRAIL as well as the drug DOX (Jiang et al, ). (c) Codelivery of the drug DOX and TRAIL‐encoding plasmid DNA via redox sensitive Tf‐targeted micelles, and hypothesized route following intravenous injection of drug/pDNA‐loaded micelles in a syngeneic tumor model (Feng et al, )…”
Section: Targeting Strategiesmentioning
confidence: 99%